Can the positions of the spastic upper limb in stroke survivors help muscle choice for botulinum toxin injections? - André Luiz Salcedo Gomes; Francisco Falleiros de Mello; Jorge Cocicov Neto; Marcelo Causin Benedeti; Luis Felipe Miras Modolo; Marcelo Riberto (Arquivos de Neuro-Psiquiatria)
ABSTRACT Motor impairments in stroke survivors are prevalent and contribute to dependence in daily activities, pain and overall disability, which can further upper-limb disability. Treatment with botulinum toxin A (BoNT-A) is indicated for focal spasticity and requires knowledge of biomechanics and anatomy to best select muscles to be injected in the limb. Objective: We aimed to describe the frequency of posture patterns in a Brazilian sample of stroke survivors and correlate them with recommendations of muscle selection for treatment with BoNT-A. Methods: Fifty stroke patients with spastic upper limbs scheduled for neuromuscular block were photographed and physically examined, to be classified by three independent evaluators according to Hefter's classification. Muscles that were injected with BoNT-A by their routine doctors were retrieved from medical charts. Results: Pattern III and IV were the most common (64.7%, 21.6%). We further subclassified pattern III according to the rotation of the shoulder, which effectively interfered in muscle choice. The muscles most frequently treated were shoulder adductors and internal rotators, elbow flexors and extensors, in forearm, the pronator teres and finger and wrist flexors, and, in the hand the adductor pollicis. Conclusion: Frequencies of upper-limb postures differed from previous reports. Other clinical features, besides spasticity, interfered with muscle choice for BoNT-A injection, which only partially followed the recommendations in the literature.